A Administração Pública na Constituição de 1988. Trinta anos depois: disputas, derrotas e conquistas = Public Administration’s ruling in the 1988 Brazilian Constitution. Thirty years by now: disputes, defeats and achievements - Baptista, Patrícia (2019)
Submitted by Iury Batista (iurys@stj.jus.br) on 2018-12-14T17:24:40Z No. of bitstreams: 2 administracao_publica_constituicao_baptista.pdf: 1022776 bytes, checksum: 21863a45c5803895748dc6f7105a578b (MD5) license.txt: 1239 bytes, checksum: c9b4c351324448672315a00808efb725 (MD5)